Molecular profiles of response to neoadjuvant chemoradiotherapy in oesophageal cancers to develop personalized treatment strategies. Issue 4 (23rd February 2021) - de Klerk, Leonie K.; Goedegebuure, Ruben S. A.; van Grieken, Nicole C. T.; van Sandick, Johanna W.; Cats, Annemieke; Stiekema, Jurrien; van der Kaaij, Rosa T.; Farina Sarasqueta, Arantza; van Engeland, Manon; Jacobs, Maarten A. J. M.; van Wanrooij, Roy L. J.; van der Peet, Donald L.; et al.
Abstract : Identification of molecular predictive markers of response to neoadjuvant chemoradiation could aid clinical decision‐making in patients with localized oesophageal cancer. Therefore, we subjected pretreatment biopsies of 75 adenocarcinoma (OAC) and 16 squamous cell carcinoma (OSCC) patients to targeted next‐generation DNA sequencing, as well as biopsies of 85 OAC and 20 OSCC patients to promoter methylation analysis of eight GI‐specific genes, and subsequently searched for associations with histopathological response and disease‐free (DFS) and overall survival (OS). Thereby, we found that in OAC, CSMD1 deletion (8%) and ETV4 amplification (5%) were associated with a favourable histopathological response, whereas SMURF1 amplification (5%) and SMARCA4 mutation (7%) were associated with an unfavourable histopathological response. KRAS (15%) and GATA4 (7%) amplification were associated with shorter OS. In OSCC, TP63 amplification (25%) and TFPI2 (10%) gene promoter methylation were associated with an unfavourable histopathological response and shorter DFS ( TP63 ) and OS ( TFPI2 ), whereas CDKN2A deletion (38%) was associated with prolonged OS. In conclusion, this study identified candidate genetic biomarkers associated with response to neoadjuvant chemoradiotherapy in patients with localized oesophageal cancer. Abstract : Using DNA sequencing and methylation panels on pretreatment biopsies, we identified candidate molecular alterations associated with response [tumour regression grade (TRG) or survival] to neoadjuvant chemoradiotherapy in localized oesophageal adenocarcinoma (OAC) and squamous cell carcinoma (OSCC). These findings may assist approaches to further individualize oesophageal cancer treatment.